The Analysis of Viewers Reception of Toxic Relationships in Posesif, an Indonesian Film - Supriadi , Kezya Bianca; Andriano, Stefanus (Jurnal InterAct, 2024)
The film "Posesif" tells the story of the unhealthy relationships experienced by teenagers. Unhealthy relationships in Indonesia often occur both verbally and physically. The film "Posesif" narrates the relationship between two teenagers that starts sweet and happy but gradually turns into an unhealthy relationship involving physical violence. This research aims to find and analyze the reception of toxic relationships as viewers perceive after watching the film "Posesif". The theories used in this research are mass communication, film, reception analysis, and interpersonal communication. This research employs a descriptive qualitative method using Stuart Hall's reception analysis. This study's data collection techniques included in-depth interviews using semi-structured interviews with seven informants, observation, and document studies. The results of this study indicate that five informants were categorized as dominant-hegemonic, two informants fell into the negotiated position, but no informants were categorized as oppositional positional. According to the informants, the film "Posesif" has successfully represented unhealthy relationships, although some informants felt that the ending of the film "Posesif" was unsatisfactory.